Models which explain the inhibition of reverse transcriptase by HIV-1-specific (thio)carboxanilide derivatives. - Esnouf, R; Stuart, D; De Clercq, E; Schwartz, E; Balzarini, J (1997)
The (thio)carboxanilide derivatives are potent and selective inhibitors of HIV-1 reverse transcriptase (RT) and have a favourable antiviral activity spectrum. To understand better their mode of action, and to provide a structural basis for further improvement, models of RT complexed with four (thio)carboxanilide inhibitors (UC781, UC10, UC38 and UC84) have been constructed based on the X-ray structure of RT complexed with 9-chloro-TIBO. In the models, the protein conformation is similar to that of the RT-TIBO complex and the complexes are stabilised by hydrogen bonding between the inhibitors and the main chain oxygen of Lys101. Significant hydrophobic interactions include those with Leu100, Val106, Val179, Tyr188, Phe227, Leu234, and His235. The thiocarboxanilides UC781 and UC10 also make important hydrophobic interactions with Trp229. The models are consistent with the inhibitors' relative antiviral potencies and the observed resistance data. They further predict that mutations to Phe227, Trp229, or Leu234 might confer resistance. Since these are not observed, some constraining structural or functional role for these residues in the active enzyme is suggested.